Risk Factors for Fungal Prosthetic Joint Infection - T. Riaz; T. Riaz; A. J. Tande; L. L. Steed; H. A. Demos; C. D. Salgado; D. R. Osmon; C. E. Marculescu (Journal of Bone and Joint Infection, 2020)
Background: Fungal prosthetic joint infections (PJIs) are rare and often associated with poor outcome; however, risk factors are not well described. Methods: This was a retrospective case control study among all patients with PJIs from 2006-2016 at two major academic centers. Each fungal PJI case was matched 1:1 with a bacterial PJI control by joint (hip, knee, shoulder) and year of diagnosis. We compared demographics, comorbidities, and clinical characteristics between cases and controls using chi square/Fisher's exact or Wilcoxon rank sum test. Independent risk factors were identified with multivariable logistic regression. Results: Forty-one fungal PJIs occurred over the study and 61% were due to Candida albicans. The hip was involved in 51.2% of cases, followed by the knee (46.3%). Compared to bacterial PJI, fungal PJI cases were more likely to have received antibiotics within the previous 3 months (70.7% vs 34%, P=.001), wound drainage lasting >5 days (48% vs 9%, P=.0002), had a lower median CRP (2.95 mg/dl vs 5.99, P=.013) and synovial fluid white blood cell count (13,953 cells/mm3 vs 33,198, P=.007), and a higher proportion of prior two-stage exchanges (82.9% vs 53.6%, P=.008). After controlling for center, prolonged wound drainage (OR, 7.3; 95% CI, 2.02-26.95) and recent antibiotics (OR, 3.4; 95% CI, 1.2-9.3) were significantly associated with fungal PJI. Conclusion: In our study, Candida albicans was the most common species in fungal PJIs and prolonged wound drainage and recent antibiotics were independent risk factors. These clinical characteristics may help providers anticipate fungal PJI and adjust management strategies.